A case of anomalous aortic origin of coronary arteries from the opposite sinus - Tanzilli, Alessandra; Griffo, Simone; Capasso, Alessandra De Luca Vincenzo; Rossi, Vincenzo; Calcagno, Marco Di Palma, Simone; Panno, Francesco; Pietro, Riccardo Di; Aisle, Pino; Versaci, Francesco (Journal of Cardiovascular Medicine and Cardiology, 2020)
Anomalous Aortic Origin of Coronary Arteries (AAOCA) is a congenital heart defect in which one coronary artery arises from the opposite sinus of Valsalva. AAOCA is observed in approximately 0.3–1.3% of patients undergoing diagnostic Invasive Coronary Angiography (ICA). Among AAOCA, anomalous origin of the left coronary artery from the right sinus of Valsalva is a relatively uncommon finding, with a reported prevalence of 0.02%-0.05% on angiographic studies. This AAOCA is the second most common cause of death in young athletes and usually occurs during exertion. Several imaging modalities have been proposed for AAOCA identiﬁcation and evaluation. Multidetector Computed Tomography (MDCT) may not only visualize AAOCA but better deﬁne, as compared with ICA, the origin and course of the anomalous vessel. We report a case of a 19 years old young athlete with anomalous origin of the Left Main Coronary Artery (LMCA) from the right sinus of Valsalva that was detected by MDCT using prospective ECG gating and low-radiation exposure.